Evaluation of microcurrent as an adjunct to donepezil therapy in an Alzheimer’s disease mouse model: a pilot study - Kim, Eun Ho; Lee, Yoon-Jin; Moon, Yong Suk; Kwon, Oh Dae; Kwon, Dong Rak (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is a neurodegenerative disorder due to Aβ plaque accumulation, followed by loss of synapses and decline in cognitive abilities. Donepezil is currently one of the standard pharmacological treatments for Alzheimer’s disease. Recently, microcurrent (MC) therapy has emerged as a non-pharmacological adjunct for AD management. Recently, microcurrent therapy emerged as a non-pharmacological alternative to treat AD.ObjectiveThe study investigates the therapeutic outcomes of the MC as an adjuvant to donepezil in mitigating cognitive dysfunction in the transgenic mouse model (5XFAD).MethodsTransgenic 5xFAD mice were assigned to the control, donepezil, MC, or MC + donepezil (combination) groups. Behavioral performance was assessed using the novel object recognition (NOR) and radial arm maze (RAM) tests. Amyloid burden, glial activation, cytokine expression, apoptotic signaling, and intracellular pathways (PI3K–AKT, AMPK, and JAK2/3) were analyzed by immunohistochemistry and Western blotting.ResultsCombined treatment with donepezil and microcurrent showed a trend toward improved cognitive performance and reduced pathology compared to donepezil alone, although these differences were not statistically significant. Aβ plaque burden in the cortex and the hippocampus was reduced by approximately 68%, thereby exceeding reductions observed with either treatment alone. Microglial and astroglial activation (Iba1, GFAP, and CD68) and pro-inflammatory cytokines (TNF-α and IL-1β) were reduced in both the donepezil and combination groups compared with untreated 5xFAD mice, with no significant difference between 5xD and 5xD + MC. Apoptotic markers (cleaved caspase-3 and cleaved PARP) were significantly reduced in both treatment groups compared with untreated controls but not significantly different between donepezil and combination therapy. At the molecular level, both donepezil and combination therapy activated PI3K–AKT and AMPK signaling and increased inhibitory phosphorylation of GSK-3β compared with untreated 5xFAD mice; no significant difference was observed between the two treatment groups.ConclusionDonepezil combined with microcurrent therapy showed comparable efficacy to donepezil alone, with numerical trends toward further improvement in cognitive function and pathology, but without statistically significant differences. Both treatments reduced Aβ burden, attenuated glial activation, and modulated survival-related pathways to a similar extent. These findings support a multi-target therapeutic strategy and highlight the translational potential of integrating microcurrent therapy with standard pharmacological treatment for AD.